2006
DOI: 10.1007/s00024-006-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Experiments of Rock Failure Under Load Simulating the Hypocenter Condition

Abstract: A series of acoustic emission (AE) experiments of rock failure have been conducted under cyclic load in tri-axial stress tests. To simulate the hypocenter condition the specimens are loaded by the combined action of a constant stress, intended to simulate the tectonic loading, and a small sinusoidal disturbance stress, analogous to the Earth tide induced by the Sun and the Moon. Each acoustic emission signal can indicate the occurrence time, location and relative magnitude of the damage (micro-crack) in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…YIN et al, 1995WANG et al, 2004;YU et al, 2010YU et al, , 2011ZHANG et al, 2006aZHANG et al, , c, 2010. Prior to occurrence of a large earthquake, the LURR time series usually climb to an anomalously high value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YIN et al, 1995WANG et al, 2004;YU et al, 2010YU et al, , 2011ZHANG et al, 2006aZHANG et al, , c, 2010. Prior to occurrence of a large earthquake, the LURR time series usually climb to an anomalously high value.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first complete stressstrain curve was obtained by Cook in 1963(COOK, 1963, large numbers of rock failure experiments were undertaken to study the rock progressive failure process (LOCKNER and BYERLEE, 1977;HSU et al, 1977;CERANOGLU and PAO, 1981). To simulate the nature failure process of rock samples, the artificial triaxial tests are introduced in experimental investigations YU et al, 2006;ZHANG et al, 2006a). The results showed that unstable point was found after the peak strength point in the complete stress-strain curve.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the rock specimens and the arrangement of the AE sensor are shown in Figure 4, while the loading process and AE event rate and energy rate versus time for the specimen are shown in Figure 5. The evolution of LURR during the rock fracture experiment has been analyzed in terms of Equation (3) of the samples and the correlationship between the AE and the load are also studied by Zhang [25][26][27][28]. Figure 6 shows the curve of LURR value versus time during rock fracture experiment for the specimen in terms of Equation (3).…”
Section: Experimental Analysismentioning
confidence: 99%
“…Our group has carried out AE experiments for medium scale rock specimens by means of international cooperation [10,[25][26][27][28]. The dimensions of the specimens are 300 mm × 360 mm × 25 mm.…”
Section: Experimental Analysismentioning
confidence: 99%
“…The picture on the left is the result of seismic data (Loma Preita earthquake) [12], the middle one is an experimental result of rock specimen [8,17] and the one on the right is an analytical result in terms of damage mechanics [18].…”
Section: The Peak Point Of Lurr and Its Significancementioning
confidence: 99%